The role of support in wrestling with cancer - Kamińska, Marzena; Bronikowska, Agnieszka; Ferańska, Maria; Paśnik, Elwira; Dziurko, Jolanta; Baczewska, Bożena (Medical Studies/Studia Medyczne, 2014)
The support provided to patients with cancer is an important determinant of their sense of security and quality of life at all stages of diagnosis, treatment, rehabilitation, remission or progression of the disease. The support is complex; its nature and scope depend on the current needs of the people who receive it. The subjective dimension of the support given to oncology patients offer sample opportunities to address the psychological impact, overcoming stress, a pathy and feelings of lesser self-esteem and use less ness. The level of support very often determines the level of optimistic attitude to life of patients and influences their motivation to fight with the disease.